Gamma radiation increases endonuclease-dependent L1 retrotransposition in a cultured cell assay - Farkash, Evan A. (Oxford University Press, 2006)
Long Interspersed Elements (LINE-1s, L1s) are the most active mobile elements in the human genome and account for a significant fraction of its mass. The propagation of L1 in the human genome requires disruption and repair of DNA at the site of integration. As Barbara McClintock first hypothesized, genotoxic stress may contribute to the mobilization of transposable elements, and conversely, element mobility may contribute to genotoxic stress. We tested the ability of genotoxic agents to increase L1 retrotransposition in a cultured cell assay. We observed that cells exposed to gamma radiation exhibited increased levels of L1 retrotransposition. The L1 retrotransposition frequency was proportional to the number of phosphorylated H2AX foci, an indicator of genotoxic stress. To explore the role of the L1 endonuclease in this context, endonuclease-deficient tagged L1 constructs were produced and tested for their activity in irradiated cells. The activity of the endonuclease-deficient L1 was very low in irradiated cells, suggesting that most L1 insertions in irradiated cells still use the L1 endonuclease. Consistent with this interpretation, DNA sequences that flank L1 insertions in irradiated cells harbored target site duplications. These results suggest that increased L1 retrotransposition in irradiated cells is endonuclease dependent. The mobilization of L1 in irradiated cells potentially contributes to genomic instability and could be a driving force for secondary mutations in patients undergoing radiation therapy.